Analysis of the velocity changes of the Jakobshavn Glacier based on SAR imagery - Łukosz, Magdalena; Hejmanowski, Ryszard; Witkowski, Wojciech T. (Quaestiones Geographicae, 2022)
The study analyzes the changes in dynamics of the Jakobshavn Glacier in summer and winter in 2017 and 2021. Satellite radar observations and the available database were used for this. Moreover, the influence of the time baseline between SAR images on the quality of the results was also investigated. The velocities computed from Sentinel-1 images and the offset-tracking technique were compared with the MEaSUREs database information. The results showed that Jakobshavn Glacier accelerated in 2021 up to 39.0 m d−1. However, this value may be underestimated due to the resolution of Sentinel-1 data. The results therefore confirm the acceleration of the glacier melting process, which may be a result of the observed climate changes on our planet.